“Marica”: A Story-Based Motion-Comic Learning Media to Improve Students’ Mathematical Representation - Chrisnawati, Henny Ekana; Pinilih, Anggoro Canggih; Nurhasanah, Farida; Usodo, Budi; Sutopo, Sutopo; Kuswardi, Yemi (Jurnal Pendidikan Progresif, 2024)
Abstract: "Marica": A Story-Based Motion-Cartoon Learning Media to Improve Students' Mathematical Representation Ability. This research is based on students' difficulties in presenting mathematical ideas and problem-solving, as well as their generally low positive attitudes towards mathematics. The researchers conducted an experimental study to examine the influence of MARICA media on students' mathematical representation abilities in the field of plane geometry. Additionally, the research aims to improve students’ mathematical representation based on various levels of mathematical logical intelligence using MARICA as a learning media. MARICA, an abbreviation for "Mari Membaca" integrates literacy concepts, engaging learning media, and story-telling. The quantitative descriptive research involved 56 first-grade elementary school students and measured both the cognitive (mathematical representation ability) and affective domains. Mathematical representation abilities were analyzed using two-way ANOVA, while affective domain data were analyzed descriptively. The results indicate a positive effect of MARICA on the mathematical representation abilities of first-grade students, with higher levels of mathematical logical intelligence correlating with better performance. Student responses to MARICA showed an increase in aspects of independence, critical attitudes, and creativity. It can be concluded that MARICA can be used to improve students’ mathematical representation and it works better for students who has good mathematical logical intelligence.Keywords: MARICA, mathematical representation, mathematical logical intelligence.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202424